A Long-Term Clinical and Cephalometric Study of Cleft Lip and Palate Patients following Intraoral Maxillary Quadrangular Le Fort I Osteotomy. (May 2015) - Karabekmez, Furkan E.; Keller, Eugene E.; Stork, James T.; Regennitter, Frederick J.; Bite, Uldis
Objective: To evaluate the horizontal and vertical stability of the quadrangular Le Fort I in patients with congenital cleft lip and palate. Design: Prospective longitudinal study. Patients: A total of 15 congenital cleft lip and palate patients treated with the maxillary quadrangular Le Fort I were enrolled. Intervention: Lateral cephalometric radiographic examinations were obtained preoperatively, early postoperatively, and late postoperatively for four dental and skeletal landmarks. A questionnaire regarding patients' satisfaction with treatment and functional/cosmetic outcomes (airway, speech, mastication) was administered. Main Outcome Measures: Surgical horizontal and vertical movement, late postsurgical horizontal and vertical movement, and surgical and postsurgical movement in relation to age and cleft type were evaluated using Spearman correlation coefficients, Wilcoxon signed rank tests, and Mann-Whitney tests. Results: Surgical horizontal movements of all measured points showed significant changes. Significant differences of postsurgical horizontal movement were observed in younger patients versus adult patients. Significant differences of postsurgical horizontal movement were observed in unilateral cleft patients versus bilateral cleft patients. A high percentage of patients showed significant functional improvement in nasal airflow, speech, mastication, temporomandibular joint function, and mouth versus nose breathing. Conclusions: The quadrangular Le Fort I is a functionally stable and a surgically predictable procedure for cleft lip and palate patients who present with midface deficiency. Patients under the age of 18 at the time of the osteotomy had a higher relapse rate than patients over 18 years of age. Younger patients who need surgery should be advised regarding the increased risk of skeletal relapse. Patients' satisfaction was high in all aesthetic- and function-related items on the questionnaire.